Microsatellite characterization and physiological changes of cryopreserved spermatozoa supplemented with antioxidants in malaysian mahseer, Tor tambra (Valenciennes, 1842) - Chew, Poh Chiang (2021)
The Malaysian mahseer that fetches the high market price and demand is now considered a prospect for aquaculture. However, a constant supply of the hatchery-produced seed and fry of Tor spp. is still minimal and inconsistent due to the lack of quality broodfish. In the present study, samples of Tor tambra and T. tambroides were collected from 11 localities in Malaysia (prior to genetic assessment) for broodstock development and sperm cryo-banking. Meanwhile, supplementation of antioxidants in the cryopreservation media is hypothesized to reduce the resulting lipid peroxidation (LPO) and oxidative stress-related DNA damages of the post-thaw sperm. As such, the objectives of this study were: 1) to establish the microsatellites (SSR) profile for the Tor spp. from different geographical regions in Malaysia; 2) to determine the effects of ascorbic acid, α-tocopherol, Trolox and reduced glutathione (GSH) on post-thaw sperm quality; 3) to investigate the effects of cryostorage duration on post-thaw sperm quality with and without antioxidants supplementation; and, 4) to assess the oxidative stress and DNA damage caused by freeze-thawing and cryostorage procedures in T. tambra sperm. Genetic characterization was conducted using 22 SSR markers via fragment analysis. Post-thaw quality of the cryopreserved sperm was assessed for sperm motion characteristics, viability, morphology and membrane plasma integrity. Effect of the cryostorage duration on post-thaw sperm quality was assessed a week after cryostorage and subsequently on a three-month basis for 12 months. The level of LPO and oxidative DNA damages after sperm cryopreservation was assessed by measuring malondialdehyde (MDA) content, 8-hydroxy-2’-deoxyguanosine (8-OHdG) concentration, DNA lesion analysis, relative sperm telomere length (STL) measurement and DNA fragmentation. In the SSR characterization, results revealed that the Tor spp. collection retained their genetic variation but exhibited excessive homozygosity. A low gene flow over all loci indicates little genetic variation transfer between populations. The genetic structure of all populations was successfully resolved into four main clusters following geographical regions. With antioxidants supplementation, the concentration that produced the best post-thaw motility in T. tambra sperm was 0.01 mM ascorbic acid, 0.025 mM α-tocopherol, 0.025 mM Trolox and 0.5 mM GSH, respectively. Overall, the motility duration of post-thaw sperm was significantly improved (p<0.05, >3 min) in treatments supplemented with antioxidants in combinations. Treatment supplemented with ascorbic acid and α-tocopherol (T5) showed the best performance with significantly (p<0.05) improved sperm motile duration, percentages of morphology, viability, morphology, reduction in LPO, 8-OHdG and DNA lesion rates while maintaining STL. Of all treatments, only treatment T3 supplemented with Trolox significantly (p<0.05) improved post-thaw sperm motility and velocity. In treatments with positive responses to antioxidants supplementation, the sperm physiology characteristics were not affected by the prolonged cryostorage period. Out of seven developmental-related genes studied, HoxC4a-2 was the most vulnerable to DNA damage. In conclusion, the findings from this study provide a significant baseline reference for the genetic status of the Tor spp. collection. New basic knowledge on LPO and oxidative DNA damage from cryostorage and improved extender formulations by exogenous antioxidants supplementation for better post-thaw quality in T. tambra sperm were generated.